Prevalence and risk factors of atopic dermatitis in Chinese children aged 1–7 years: a systematic review and meta analysis - Ma, Xueting; Xie, Zhiyin; Zhou, Yu; Shi, Hui (Frontiers in Public Health, 2024)
Introduction Atopic dermatitis (AD) is a common, chronic, recurrent inflammatory skin disease. To date, no meta-analysis have been conducted on the prevalence and risk factors of AD in children aged 1–7 years in Mainland China. Methods We conducted a meta-analysis of the prevalence and risk factors of AD among children aged 1–7 years in China. Chinese and English publications were searched in Chinese and English databases on AD epidemiology published between 1999 and 2023. Two researchers independently screened the literature, extracted the data, and evaluated their quality. A meta-analysis was performed using a random-effects model (I2 > 50%) with 95% confidence intervals (CIs) for the forest plots. Data were processed using the RevMan 5.3. Results Nineteen studies (data from 127,660 samples) met the inclusion criteria. The pooled prevalence of AD in Chinese children aged 1–7 years was 8%. Over the last decade, the prevalence of AD has increased. The prevalence of AD among children in southern China was higher than that in northern China and was the highest at the provincial level in Zhejiang, Shanxi, and Anhui. The prevalence of AD was dependent on the family history of allergy, passive smoking, households with pets, plush toys, and residential area. Discussion The prevalence of AD in children (age 1–7 years) in China has increased. Further studies are needed to monitor the prevalence of AD in Chinese children. Therefore, early prevention and screening should be performed for children with a family history of AD, and their living environment should be improved to reduce allergen stimulation, thus reducing the development of AD.